Character Education Management Based on Salafiyah Pesantren Traditions: A Comparative Study - Maryamah, Lutpa (MANAGIERE: Journal of Islamic Educational Management, 2026)
This study aims to analyze the management of character education based on salafiyah pesantren traditions in fostering students’ religiosity and entrepreneurial spirit through a comparative approach. The research was conducted at Pesantren Miftahul Huda Al-Musri’ in Cianjur and Pesantren Mardhotillah in Bandung, two Islamic boarding schools that represent different orientations within the salafiyah tradition. A qualitative descriptive design was employed, using data triangulation techniques consisting of in-depth interviews, participatory observation, and documentation. Data were analyzed through the interactive model of reduction, display, and conclusion drawing to obtain a comprehensive understanding of character education practices. The findings reveal that character education in salafiyah pesantren is implemented through structured managerial processes that integrate religious learning, habituation, exemplary leadership, and entrepreneurship programs. Both pesantren demonstrate that religiosity and entrepreneurship are complementary dimensions of Islamic character education. Pesantren Miftahul Huda emphasizes the preservation of classical traditions and spiritual discipline, while Pesantren Mardhotillah focuses on innovation by integrating entrepreneurship into the educational system. This comparative result indicates the flexibility of salafiyah traditions in responding to contemporary challenges without losing their Islamic identity. The study concludes that salafiyah pesantren traditions function as effective instruments of character education management capable of producing graduates who are religious, morally responsible, and economically independent. The novelty of this research lies in its formulation of an integrative model of character education management that connects religiosity and entrepreneurship within the framework of Islamic education management. Practically, the findings provide a reference for developing pesantren curricula that harmonize spiritual values with economic empowerment, contributing to the sustainability and relevance of pesantren education in the modern era.